Sodium ferrite particles and method for producing same

By using characteristic sodium iron particles for solid phase reaction in small and medium-sized facilities, the problems of high energy cost and complex operation of carbon dioxide capture and recovery in these facilities in the prior art are solved, and the effect of efficient fixing and restoring carbon dioxide at lower temperatures is achieved.

JP7658177B2Active Publication Date: 2025-04-08TODA KOGYO CORP
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2021091854
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-31
Publication Date
2025-04-08
Estimated Expiration
2041-05-31

AI Technical Summary

Technical Problem

The prior art methods of capturing and restoring carbon dioxide in small and medium-sized facilities have problems of high energy costs, use of hazardous materials and complex operations, especially in cases where liquid absorbers are not suitable.

Method used

Sodium iron powder with specific physical properties and composition ratios is used to generate sodium iron powder within the temperature range of 150°C to 400°C through solid phase reaction, achieving fixation and recovery of carbon dioxide. This method uses non-hazardous inorganic materials that enables the fixation of carbon dioxide at a temperature range from room temperature to 100°C and recover below 150°C.

Benefits of technology

The fixation and recovery of carbon dioxide at lower temperatures is achieved, reducing energy costs, and improving the shape variability and processing properties of the materials, making it suitable for applications in small and medium-sized facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658177000004
    Figure 0007658177000004
  • Figure 0007658177000001
    Figure 0007658177000001
  • Figure 0007658177000002
    Figure 0007658177000002
Patent Text Reader

Abstract

To provide a sodium ferrite particle powder that adsorbs carbon dioxide in a temperature range from room temperature to 100°C, can recover carbon dioxide by heating at 150°C or lower, and has superior moldability and processability, and a method for producing the particle powder.SOLUTION: A sodium ferrite particle powder contains at least one divalent metal acid sodium selected from divalent metal acid sodiums composed of Na2[Zn(OH)4] and Na2SnO2 of 1 wt.%-20 wt.% with the molar ratio of Na / Fe being 1.0-1.5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention provides sodium ferrite particles capable of immobilizing carbon dioxide and a method for producing the same. [Background technology]

[0002] The United Nations Framework Convention on Climate Change (Paris Convention) was formulated in 2015 with the goal of reducing greenhouse gas emissions, which are believed to be the cause of the rise in global average temperature, to virtually zero in order to keep the increase well below 2 degrees Celsius. In this agreement, the government's policy is to set a mid-term goal of reducing greenhouse gas emissions by 46% by 2030 compared to fiscal 2013 levels. The main greenhouse gas is carbon dioxide, which is generated by the combustion of fossil fuels. The carbon dioxide concentration in the atmosphere was approximately 300 ppm in the 1950s, but it has been reported to have exceeded 400 ppm in recent years. Research is being conducted into the capture, storage, and utilization of carbon dioxide as a trump card for reducing the amount of carbon dioxide released into the atmosphere.

[0003] Large-scale sources of carbon dioxide include exhaust gas outlets from the combustion of fossil fuels, such as thermal power plants that use coal, heavy oil, or natural gas as fuel, boilers in manufacturing plants, and kilns in cement plants. Other sources include carbon dioxide emitted from blast furnaces in steel plants that reduce iron oxide with coke, and from transportation vehicles such as automobiles, ships, and airplanes that use gasoline, heavy oil, or light oil as fuel.

[0004] Currently, in large-scale facilities such as thermal power plants, exhaust gas is brought into contact with an aqueous amine solution such as alkanolamine to absorb the carbon dioxide contained in the exhaust gas. The mixture is then heated to about 120°C to capture the absorbed carbon dioxide. These attempts have been launched on a large scale and have produced great results (Patent Documents 1-2). This method has the advantage that a liquid absorbent is used, and the absorbent can be transported by pump. This makes it easy to scale up. Amine-based carbon dioxide capture materials are being put to practical use in thermal power plants, steelworks, and other facilities.

[0005] However, this method uses a hazardous liquid, which makes it difficult for small and medium-sized facilities such as waste incineration plants, of which there are more than 1,800 in Japan, to handle such liquids. As a result, carbon dioxide fixation and capture is hardly performed at present. At present, the total carbon dioxide emissions throughout Japan are on a slight downward trend. Therefore, it is expected that carbon dioxide fixation and capture will be achieved using an inexpensive solid that is easy to handle and does not involve hazardous materials such as amines, so that even small and medium-sized facilities can fix and capture carbon dioxide.

[0006] Known solid carbon dioxide capture and fixation materials include the above-mentioned alkanolamine-supported solid (Patent Document 3), barium orthotitanate (Patent Document 4), and lithium ferrite (Patent Document 5).

[0007] Sodium ferrite (Patent Document 6, Non-Patent Documents 1 and 2) is also known as a material for capturing and fixing carbon dioxide. Among them, α-sodium ferrite, which has a layered rock salt structure (trigonal system), reacts topochemically with carbon dioxide and sodium. That is, during the reaction with carbon dioxide, α-sodium ferrite reacts with Na 1-x It becomes a mixed phase of FeO2 and sodium carbonate. Therefore, it has been reported that the reaction rate is high and the repeated absorption and release of carbon dioxide due to this reaction is excellent. On the other hand, it has been reported that the crystal phase of β-sodium ferrite with an orthorhombic crystal system reacts with sodium and carbon dioxide, so that the crystal phase of β-sodium ferrite absorbs more carbon dioxide than the crystal phase of α-sodium ferrite.

[0008] In general, the reaction formula of sodium ferrite with carbon dioxide can be written as NaFeO2+1 / 2CO2→1 / 2Na2CO3+1 / 2Fe2O3 when the gas does not contain water vapor, and NaFeO2+CO2+1 / 2H2O→NaHCO3+1 / 2Fe2O3 when water vapor is contained. Therefore, sodium ferrite has the theoretical ability to adsorb and desorb up to 18-30% by weight of carbon dioxide. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 5-301023 [Patent Document 2] JP 2009-6275 A [Patent Document 3] JP 2012-139622 A [Patent Document 4] JP 2006-298707 A [Patent Document 5] JP 2005-270842 A [Patent Document 6] JP 2016-3156 A [Non-patent literature]

[0010] [Non-Patent Document 1] I. Yanase, S. Onozawa, K. Ogasawara, H. Kobayashi, J. CO2 Utilization, Vol. 24, 2018, pp. 200-209 [Non-Patent Document 2] Ikuo Yanase, Journal of the Society of Inorganic Materials, Japan, Vol. 25, 2018, pp. 437-442 Summary of the Invention [Problem to be solved by the invention]

[0011] As described above, there are high hopes for carbon dioxide fixation and capture materials using solid, particularly non-hazardous inorganic materials. However, while the current fixation and capture of carbon dioxide using an amine aqueous solution is carried out at about 120°C, carbon dioxide fixation and capture materials using inorganic materials such as barium orthotitanate (Patent Document 4) and lithium ferrite (Patent Document 5) adsorb and desorb carbon dioxide in a temperature range of 200°C or higher, and are inferior in terms of energy cost to those using an amine aqueous solution.

[0012] That is, the methods described in Patent Documents 1 and 2 use an aqueous amine solution as a material for fixing and capturing carbon dioxide, which is advantageous for large facilities such as thermal power plants, but is not suitable for small and medium-sized facilities that emit carbon dioxide.

[0013] The material described in Patent Document 3 is also a carbon dioxide capture material containing alkanolamine, and uses alkanolamine, which is a hazardous material. Therefore, there is a concern about the leaching of the amine component, and the like, so it is not suitable for small and medium-sized facilities.

[0014] The method described in Patent Document 4 uses a Ba2TiO4-based composite oxide as a material for capturing and fixing carbon dioxide. However, since the heating temperature in the carbon dioxide release step is 800 to 1000°C, it is disadvantageous in terms of heat cost.

[0015] The system described in Patent Document 5 uses a composite oxide containing lithium and iron as a carbon dioxide fixation and capture material. However, the fixation and capture temperature of carbon dioxide is 500°C, and the release temperature is 700°C, which is disadvantageous in terms of heat cost.

[0016] The above-mentioned Patent Document 6 and Non-Patent Documents 1 and 2 report the fixation and recovery of carbon dioxide at room temperature, and also report on porous bodies. However, there is no description on the moldability or processability of the material itself.

[0017] Therefore, an object of the present invention is to provide sodium ferrite particles which can immobilize carbon dioxide in a temperature range from room temperature to 100°C and recover carbon dioxide by heating at 150°C or less, and which are highly moldable and processable, and to provide a method for producing the particles. [Means for solving the problem]

[0018] In order to achieve the above object, the present inventors conducted extensive research and discovered that by using sodium ferrite particles having predetermined physical properties and composition ratio, carbon dioxide can be immobilized in a temperature range from room temperature to 100°C and the immobilized carbon dioxide can be recovered at 150°C or less, thereby completing the present invention.

[0019] Specifically, the sodium ferrite particles according to the present invention are characterized in that they contain 1 wt % to 20 wt % of at least one kind of sodium divalent metal oxide selected from the group consisting of sodium divalent metal oxides Na2[Zn(OH)4] and Na2SnO2, and have a molar ratio of Na / Fe of 1.0 to 1.5.

[0020] The presence of the divalent metal sodium oxide makes it possible to recover the immobilized carbon dioxide at a lower temperature than pure sodium ferrite. Although the details are not clear, this is thought to be because the presence of the divalent metal sodium oxide component causes the Na ferrite that has absorbed carbon dioxide to be absorbed by the ferrite. 1-x It is considered that the mixed phase of FeO2 and sodium carbonate volatilizes carbon dioxide with a lower energy input, or catalyzes the return to sodium ferrite with a lower energy input. In addition, since the particle powder according to the present invention has a molar ratio of Na / Fe of 1.0 to 1.5, it can contain a large amount of sodium ferrite crystal phase, and the carbon dioxide fixation and recovery performance is good. Since the proportion of Na is not excessively high, alkaline components such as NaOH and Na2CO3, which are by-products that cause gelation of the paint when the particle powder is made into a paint, are less likely to remain, and the paint can be highly dispersible. Due to these characteristics, the sodium ferrite particle powder according to the present invention can fix carbon dioxide in a temperature range from room temperature to 100°C and recover the fixed carbon dioxide at 150°C or less.

[0021] The sodium ferrite particles according to the present invention preferably have an aspect ratio of the average major axis diameter to the average minor axis diameter of the primary particles of 1-2.

[0022] The particle powder has a small axis ratio of the average major axis diameter to the average minor axis diameter of the primary particles of 1 to 2, and has a shape close to a sphere. Therefore, the primary particles are highly dispersible and less likely to aggregate, resulting in a particle powder with excellent moldability and processability.

[0023] The sodium ferrite particles according to the present invention preferably have a powder pH value of 8-14.

[0024] If the powder pH value is 8 to 14, the sodium ferrite particles according to the present invention are basic and therefore easily capture carbon dioxide, which is weakly acidic. Furthermore, as described above, the by-products such as NaOH and Na2CO3, which cause gelation of the paint, are less likely to remain, so that the particles can be used as a paint with high dispersibility.

[0025] The method for producing sodium ferrite particles according to the present invention is characterized by comprising the steps of mixing at least one metal compound particle powder selected from zinc and tin, iron oxide particle powder, and sodium raw material particle powder, and subjecting the mixture to a water vapor solid-phase reaction at a temperature of 150°C to 400°C.

[0026] In the method for producing sodium ferrite particles according to the present invention, solids are mixed and reacted by transferring elements without the intervention of a solvent. Since no solvent is used as a reaction mother liquid, waste such as solvents that would be generated in a liquid-phase reaction can be reduced. In particular, in the case of a solid-phase reaction at a low temperature, a very high-concentration reaction can be achieved, so that energy costs can be reduced. Furthermore, heating with water vapor causes a trace amount of moisture to be present at the contact interface between the iron oxide and the sodium source, thereby promoting an acid-base reaction at the contact interface. In addition, the oxygen partial pressure is reduced by water vapor, so that the oxidation reaction of the iron oxide, which is a side reaction, is suppressed, and the purity is easily increased. Furthermore, the risk of fire is significantly reduced by heating with water vapor. Therefore, according to the method for producing sodium ferrite particles according to the present invention, carbon dioxide can be fixed in a temperature range from room temperature to 100° C., carbon dioxide can be recovered by heating at 150° C. or less, and sodium ferrite particles having excellent moldability and processability can be produced with high purity and high efficiency. Effect of the Invention

[0027] The sodium ferrite particles according to the present invention are non-hazardous inorganic materials that can immobilize carbon dioxide in a temperature range from room temperature to 100° C. and recover the immobilized carbon dioxide at temperatures below 150° C. In addition, the particles have excellent dispersibility after being made into a paint, and are therefore suitable as a material with excellent moldability and processability. [Brief description of the drawings]

[0028] [Figure 1] 1 shows the results of thermogravimetric analysis of carbon dioxide fixed by the sodium ferrite particles obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The configuration of the present invention will be described in more detail below.

[0030] First, a carbon dioxide capture and capture material according to one embodiment of the present invention will be described.

[0031] The sodium ferrite particles according to the present embodiment contain 1% by weight to 20% by weight of at least one kind of sodium divalent metal oxide selected from sodium divalent metal oxides consisting of Na2[Zn(OH)4] and Na2SnO2. When the content is in the above-mentioned weight percent range, the carbon dioxide fixation and recovery performance can be improved. More preferably, the weight percent range is 1% by weight to 15% by weight.

[0032] The sodium ferrite particles according to one embodiment of the present invention have a molar ratio of Na / Fe of 1.0 to 1.5. If the molar ratio of Na / Fe is less than 1.0, the resulting powder will have a low content of sodium ferrite particles, and will have poor carbon dioxide fixation and recovery performance. If the molar ratio of Na / Fe exceeds 1.5, a large amount of alkaline components such as by-products NaOH and Na2CO3 will remain. The alkaline components are also a cause of gelation of paint, and it is difficult to say that a highly dispersible paint can be produced, and it is difficult to say that the resulting particle powder has excellent moldability and processability. The molar ratio of Na / Fe is preferably 1.1 to 1.5, and more preferably 1.1 to 1.4.

[0033] The sodium ferrite particles according to one embodiment of the present invention preferably contain 80% by weight or more of the α-sodium ferrite crystal phase. The compound having the α-sodium ferrite crystal is a layered compound in which iron, oxygen, and sodium are arranged in layers, and parallel oxygen hexagonal lattices are arranged in a pattern of ABCABC. The sodium ions between the oxygen hexagonal lattices move to the surface of the α-sodium ferrite particles and react with carbon dioxide. Therefore, this reaction is said to be a topochemical reaction in which the shape of the α-sodium ferrite particles is maintained. It is preferable to contain a larger amount of the α-sodium ferrite crystal phase, since this provides excellent repeatability in the fixation and recovery of carbon dioxide. More preferably, the content of the α-sodium ferrite crystal phase is 83% by weight or more.

[0034] The sodium ferrite particles according to the present embodiment preferably have a β-sodium ferrite crystal phase of 2% by weight or less. The β-sodium ferrite crystal phase has oxygen hexagonal lattices arranged in a ABABAB pattern. The volume per mole of β-sodium ferrite is 1.3 times higher than that of α-sodium ferrite, and the bond strength between atoms is expected to be weak, and the crystal structure is expected to easily collapse. Therefore, if the β-sodium ferrite crystal phase exceeds 2% by weight, it is not preferable in terms of carbon dioxide repeatability.

[0035] The sodium ferrite particles according to the present embodiment preferably contain 2% by weight or less of the unreacted magnetite phase or maghemite phase. An increase in the unreacted phase is undesirable because it reduces the carbon dioxide capture performance.

[0036] The sodium ferrite particles according to the present embodiment preferably have a powder pH of 8 to 14. The powder pH of 8 or more is basic, and therefore carbon dioxide, which is weakly acidic, can be easily captured. On the other hand, if the powder pH exceeds 14, the paint will gel, making it difficult to achieve high dispersibility. More preferably, the powder pH is 11.8 to 13.5.

[0037] The sodium ferrite particles according to the present embodiment have a BET specific surface area of ​​1 m 2 / g~8m 2 / g. It is preferable that the BET specific surface area is 1 m 2 If the BET specific surface area is less than 8 m / g, the carbon dioxide contained in the gas is less likely to come into contact with the gas, and the carbon dioxide absorption performance is reduced. 2 If the BET specific surface area exceeds 1.5 m / g, industrial production becomes difficult. 2 / g~7.8m 2 / g. Even more preferably, it is 2.0m 2 / g~7.5m 2 / g.

[0038] The sodium ferrite particles according to the present embodiment preferably have an average primary particle diameter of 50 nm to 1000 nm. If the average primary particle diameter is less than 50 nm, industrial production becomes difficult. If the average primary particle diameter exceeds 1000 nm, the carbon dioxide absorption performance decreases. More preferably, the average primary particle diameter is 100 nm to 700 nm.

[0039] The sodium ferrite particles according to this embodiment preferably have an axial ratio (average major axis diameter / average minor axis diameter) of the primary particles of 1.0 to 2.0. If the axial ratio exceeds 2, the primary particles tend to aggregate, making it difficult to maintain high dispersibility after coating. As a result, the particle powder is not excellent in moldability and processability. In addition, the axial ratio cannot be smaller than 1. The axial ratio is more preferably in the range of 1.05 to 1.9, and even more preferably in the range of 1.1 to 1.8.

[0040] When the sodium ferrite particles according to this embodiment are applied as a carbon dioxide fixation and recovery material, they can selectively adsorb and fix carbon dioxide from a gas containing carbon dioxide. The adsorption temperature is from room temperature to the exhaust gas outlet temperature, that is, about 10°C to 100°C. More preferably, it is about 10°C to 50°C. Since no additional heating from the outside is required, the energy cost required for adsorption can be kept low (above, carbon dioxide fixation process).

[0041] The sodium ferrite particles according to this embodiment preferably desorb the carbon dioxide taken in in the carbon dioxide fixation step at a temperature higher than 50° C. and not higher than 150° C. in a gas atmosphere not containing carbon dioxide, and recover the carbon dioxide. The low desorption temperature of not higher than 150° C. reduces the energy cost required for desorption (referred to as the carbon dioxide recovery step).

[0042] The sodium ferrite particles according to this embodiment can control the superficial velocity of an adsorption tower when contacted with carbon dioxide as a carbon dioxide fixation and capture material. That is, the sodium ferrite particles may be granulated or supported on a carrier to form a spherical molded body having a diameter of about 100 μm to 10 mm. More preferably, the spherical molded body has a diameter of 200 μm to 7 mm. This is because the molded body containing the sodium ferrite particles is sized to a diameter of 1 m so as not to impede contact with carbon dioxide even if the diameter of the molded body becomes large. 2 / g~1000m 2 The molded body preferably has a specific surface area of ​​100 / g. The shape of the molded body is not particularly limited, but is preferably a spindle shape, a rectangular parallelepiped shape, a cube shape, or the like, in addition to a sphere. The sodium ferrite particles may be made into a paint and applied to a mesh, nonwoven fabric, honeycomb, or the like to fix and collect carbon dioxide, or the sodium ferrite particles may be packed into a column to make a filter to fix and collect carbon dioxide.

[0043] Next, a method for producing the sodium ferrite particles according to an embodiment of the present invention will be described.

[0044] The sodium ferrite particles according to the present embodiment can be obtained by mixing at least one metal compound particle powder selected from a group of divalent metals consisting of zinc and tin, iron oxide particle powder, and sodium raw material particle powder, and carrying out a solid-phase reaction by heating with steam at a temperature of 150° C. to 400° C. By mixing the raw materials in this manner and carrying out a solid-phase reaction, the divalent metal becomes a sodium divalent metal oxide such as Na2[Zn(OH)4] or Na2SnO2.

[0045] When the above-mentioned metal compound particles, iron oxide particles, and sodium raw material particles were subjected to a solid-state reaction, the divalent metal components contained in the metal compound particles tended to suppress the growth of the primary particles of sodium ferrite. As a result, the particles had a large BET specific surface area, which is preferable as a material for fixing and capturing carbon dioxide. In addition, as a characteristic of the solid-state reaction, the crystal growth of sodium ferrite tends to be isotropic, so the axial ratio of the primary particles tends to be suppressed.

[0046] The content of sodium divalent metal oxide such as Na2[Zn(OH)4] or Na2SnO2 is preferably 1% by weight to 20% by weight. As described above, this is because it may improve the carbon dioxide fixation and recovery performance. The content of the sodium divalent metal oxide is more preferably 2% by weight to 15% by weight.

[0047] As the iron oxide particle powder, hematite, magnetite, maghemite, goethite, etc. can be used. In order to contain a large amount of the crystalline phase of α-sodium ferrite, magnetite and maghemite with a spinel structure in which the oxygen hexagonal lattice has the same ABCABC pattern as the crystalline phase of α-sodium ferrite are preferred. (Reference: Shoichi Okamoto, "Crystal Formation and Phase Transition of Sodium Orthoferrite", Nagaoka University of Technology Research Report No. 8 (1986) pp. 37-42)

[0048] The shape of the iron oxide particles can be selected from needle, spindle, granular, spherical, tetrahedral, hexahedral, octahedral and the like.

[0049] The particle diameter of the iron oxide particles can be selected from any size ranging from 10 nm to 1 μm.

[0050] As the particle powder of the sodium raw material, sodium nitrite, sodium sulfate, sodium carbonate, sodium hydrogen carbonate, sodium hydroxide, sodium oxide, etc. can be used. However, when considering industrial use, sodium nitrite, sodium sulfate, etc., which may generate toxic nitrous acid gas, sulfurous acid gas, etc. during production, should be avoided.

[0051] As the metal compound particles of at least one kind selected from the group consisting of divalent metals consisting of zinc and tin, oxides, hydroxides, chlorides, carbonates, etc. of various metals may be used as raw materials. Also, composites of the above metals may be used.

[0052] In general, solid-phase reactions are synthesis methods in which solids are mixed and reacted by transferring elements without the use of a solvent. Since no solvent is used as the reaction mother liquid, waste such as solvents that would be generated in a liquid-phase reaction can be reduced. In addition, in the case of a solid-phase reaction at a low temperature, which is a feature of the present invention, an extremely high-concentration reaction can be achieved, so energy costs can be kept low. In addition, since there is no need for the high reaction concentration or washing, a high yield of the product can be expected.

[0053] In addition, in the solid-phase reaction using water vapor as a heat source, the presence of a small amount of moisture at the contact interface between the iron oxide and the sodium source promotes an acid-base reaction at the contact interface, resulting in a high-purity sodium ferrite with significantly less unreacted products such as magnetite phase or maghemite phase, which is preferable.

[0054] In addition, in a solid-state reaction at 400°C or less using steam as a heat source, heat is transferred uniformly to the contact interface between the iron oxide and the sodium source, so that the crystal phase of the sodium ferrite produced becomes a highly pure α-sodium ferrite phase, which is preferable.

[0055] <effect> In this embodiment, the sodium ferrite particle powder containing 1% by weight to 20% by weight of at least one or more kinds of sodium divalent metal oxides selected from sodium divalent metal oxides consisting of Na2[Zn(OH)4] and Na2SnO2 further has the excellent property of adsorbing carbon dioxide in the gas, trapping it in the solid, and releasing the carbon dioxide when heated. These make it possible to recover the fixed carbon dioxide at a lower temperature than pure sodium ferrite. Although the details are not clear, this is thought to be because the presence of these sodium divalent metal oxide components causes the Na ferrite that has taken in carbon dioxide to absorb the carbon dioxide. 1-xIt is considered that the mixed phase of FeO2 and sodium carbonate volatilizes carbon dioxide with lower energy input, or catalyzes the return to sodium ferrite with lower energy input. In addition, since the particle powder according to this embodiment has a molar ratio of Na / Fe of 1.0 to 1.5, it can contain a large amount of sodium ferrite crystal phase, and the carbon dioxide fixation and recovery performance is good. Since the proportion of Na is not excessively high, alkaline components such as NaOH and Na2CO3, which are by-products that cause gelation of the paint when the particle powder is made into a paint, are less likely to remain, and the paint can be highly dispersible. Due to these characteristics, the sodium ferrite particle powder according to this embodiment can fix carbon dioxide in a temperature range from room temperature to 100°C and recover the fixed carbon dioxide at 150°C or less. EXAMPLES

[0056] A typical embodiment of the present invention is as follows.

[0057] The sodium ferrite particles according to the present invention and the raw materials thereof were subjected to elemental analysis (excluding oxygen) using a scanning X-ray fluorescence analyzer ZSX PrimusII manufactured by Rigaku Corporation.

[0058] The weight percentage of the crystalline phase of the sodium ferrite particles according to the present invention was identified and quantified by a fully automatic multipurpose X-ray diffractometer D8 ADVANCE manufactured by BRUKER.

[0059] The BET specific surface area of ​​the sodium ferrite particles according to the present invention was measured by the BET method using nitrogen and a Multisorb-16 manufactured by QUANTA CHROME.

[0060] The average major axis diameter and the average minor axis diameter of the primary particles of the sodium ferrite particles according to the present invention were calculated by measuring the major axis diameter and the minor axis diameter of 350 primary particles shown in a micrograph taken with a scanning electron microscope S-4800 manufactured by Hitachi High-Technologies, and expressing the average values ​​thereof.

[0061] The aspect ratio of the sodium ferrite particles according to the present invention is shown as the ratio of the average major axis diameter to the average minor axis diameter (average major axis diameter / average minor axis diameter).

[0062] The average primary particle size of the sodium ferrite particles according to the present invention is expressed as the average value of the average major axis diameter and the average minor axis diameter.

[0063] The powder pH value of the sodium ferrite particles according to the present invention was determined by weighing 5 g of a sample into a 300 ml Erlenmeyer flask, adding 100 ml of boiled pure water, heating and maintaining the boiled state for about 5 minutes, then plugging and allowing to cool to room temperature, adding water equivalent to the weight lost, plugging again, shaking for 1 minute, and leaving to stand for 5 minutes. The pH of the resulting supernatant was measured according to JIS Z8802-7, and the obtained value was taken as the powder pH value.

[0064] The carbon dioxide fixation and recovery capacity of the sodium ferrite particles according to the present invention was evaluated by placing 100 mg of a sample on a combustion boat, putting it in an acrylic pipe equipped with inlet and outlet piping, introducing a (carbon dioxide + nitrogen) mixed gas adjusted to a humidity range of 20 to 100% and a carbon dioxide concentration range of 1 to 100 vol% from the inlet at 500 mL / min, and measuring the amount of carbon dioxide adsorption after 2 hours by heating the sample from room temperature to 200°C using a Hitachi High-Tech simultaneous differential thermal and thermogravimetric analyzer STA7000. The amount of carbon dioxide fixation and recovery was calculated from the heat loss.

[0065] To evaluate the dispersibility of the sodium ferrite particles according to the present invention, 10 parts by weight of sodium ferrite powder was weighed, and 1 part by weight of alkylamine, 89 parts by weight of propylene glycol monomethyl ether acetate, and 100 parts by weight of 1.5 mm glass beads were added. The mixture was then shaken for 2 hours in a paint conditioner, and the glass beads were filtered out and removed from the slurry. The dispersed particle size of the obtained slurry was measured using a concentrated particle size analyzer FPAR1000 manufactured by Otsuka Electronics. When the cumulative 50% value (D50) of the scattering intensity distribution was 2 times or less than the average primary particle size, the sample was judged to have good dispersibility and was marked with "◯", and when it exceeded 2 times, it was marked with "X".

[0066] <Method of manufacturing sodium ferrite particles> Example 1 Iron oxide fine particles 1 (Toda Kogyo 100ED, hematite, specific surface area 11 m 2 The sodium hydroxide particle powder as the sodium raw material was weighed out so that the molar ratio of Na / Fe was 1.2, and 1.0 part by weight (10% by weight based on the iron oxide) was weighed out and added. After mixing the raw materials, the mixture was mixed and pulverized in a sample mill. The mixed and pulverized material was placed in a crucible and subjected to a water vapor solid-phase reaction at 250°C for 16 hours. The mixture was then cooled to room temperature and pulverized in a sample mill to obtain sodium ferrite particle powder. The BET specific surface area of ​​the obtained particle powder was 4.0 m 2 / g. Quantification of the primary particles by scanning electron microscopy revealed that the average major axis diameter was 0.5 μm, the average minor axis diameter was 0.3 μm, the average primary particle diameter was 0.4 μm, and the axial ratio was 1.7. The powder pH was relatively high at 13.4.

[0067] Elemental analysis of the obtained sodium ferrite particles by X-ray fluorescence revealed that the molar ratio of Na / Fe was 1.2, and the powder was found to be 90% by weight of α-sodium ferrite, 2% by weight of β-sodium ferrite, 1% by weight of maghemite, and 7% by weight of Na2[Zn(OH)4] by quantification of the powder X-ray diffraction pattern. Also, some of the added zinc did not appear in the powder X-ray diffraction, and is considered to be incorporated into the sodium ferrite phase in an amorphous or non-specific crystalline state.

[0068] In order to examine the carbon dioxide fixation and recovery performance of the obtained sodium ferrite particles, 1.00 weight part of the sample was placed on No. 2 combustion boat (12 x 60 x 9 mm) and aerated with model combustion exhaust gas at 500 mL / min for 3 hours. In general, the exhaust gas from burning fuel in the atmosphere is composed of a maximum of 80 vol% nitrogen, 20 vol% carbon dioxide, and 80 to 100% humidity. Therefore, at room temperature of 25°C, 400 mL / min of nitrogen and 100 mL / min of carbon dioxide were mixed and bubbled into water to obtain a model combustion exhaust gas with 20 vol% carbon dioxide and a relative humidity of 80%.

[0069] After aeration, 10 mg of the sample was weighed, and the sample was heated to 200°C at 10°C / min while being aerated with 300 mL / min of dry air using a thermogravimetric analyzer, and the desorption temperature and amount of carbon dioxide adsorbed by the sample were measured. Figure 1 shows a measurement chart with the sample temperature on the horizontal axis. The TG curve is the weight percent of the remaining sample at each temperature when the initial weight is 100%, and the amount of the sample reduced was considered to be due to the release of carbon dioxide. The DTG curve is a differential curve of the TG curve, and the temperature at which the DTG curve has a maximum value was considered to be the desorption temperature of carbon dioxide. The DTA curve showed a downward convex curve, and it was found that an endothermic reaction was taking place around 99°C. When this was quantified as a thermal decomposition reaction of NaHCO3, the carbon dioxide desorption temperature was 93°C, and the amount of carbon dioxide desorption was 8% by weight of the sample solid content, demonstrating excellent carbon dioxide fixation and recovery performance.

[0070] Furthermore, the sample after aeration was reprepared and weighed, which was 1.20 parts by weight, confirming a mass increase of 20% by weight. X-ray diffraction of this sample revealed that it was a sodium-deficient type Na 1-xFeO2, Na2[Zn(OH)4], and NaHCO3 were confirmed, and it was found that carbon dioxide was fixed in the sodium ferrite particle powder. Furthermore, when this sample was heated in an electric furnace at 100°C for 1 hour and the weight was measured, it was 1.12 parts by weight, and it was found that 0.08 parts by weight (8% by weight based on the solid content) of carbon dioxide could be adsorbed and desorbed in this cycle. Furthermore, when this sample was contacted with carbon dioxide as described above, the weight increased to 1.20 parts by weight, and when heated, the weight decreased to 1.12 parts by weight, and 0.08 parts by weight of carbon dioxide could be adsorbed and desorbed. This operation was repeated 10 times, and it was confirmed that there was no change in the increase and decrease in mass. From this, it was revealed that the sodium ferrite particle powder has excellent carbon dioxide fixation and recovery performance, especially excellent repeatability.

[0071] The dispersibility of the obtained sodium ferrite particles was evaluated, and it was found to be good, with the dispersed particle diameter being within twice the average primary particle diameter.

[0072] Examples 2 to 6 Sodium ferrite particles according to the present invention were obtained in the same manner as in Example 1, except that the types and amounts of the iron oxide fine particles, the sodium source, and the metal compound were variously changed.

[0073] The production conditions in these examples are shown in Table 1, the properties of the obtained sodium ferrite particles in Table 2, and the carbon dioxide fixation and recovery performance and dispersibility in Table 3. The carbon dioxide recovery performance was evaluated by placing 10 g of the carbon dioxide absorbent in a desiccator (13 L) with a carbon dioxide concentration of 4000 ppm, and grading the carbon dioxide concentration of 2500 ppm or less after 30 minutes as ○ and the carbon dioxide concentration exceeding 2500 ppm as ×. Samples with good dispersibility are marked with ○, and those without are marked with × in Table 3.

[0074] Comparative Example 1 The iron oxide 1 was used as 10 parts by weight, and sodium hydroxide particle powder was weighed out to give a molar ratio of Fe:Na of 1:1. 100 parts by weight of pure water was added to dissolve the sodium hydroxide particle powder, and the mixture was kneaded for 2 hours in an automatic mortar. The mixture was dried at 80°C for 2 hours, and mixed and ground in a sample mill. The mixed and ground product was placed in a crucible and heat-treated at 400°C for 16 hours. Powder X-ray diffraction revealed that the product was 25% by weight of α-sodium ferrite crystal phase and the remaining 75% by weight of γ-Fe2O3 crystal phase. The BET specific surface area was 1.0 m 2 The carbon dioxide fixation and recovery performance was examined in the same manner as in the examples, and the temperature was raised to 200° C., but desorption of carbon dioxide was not confirmed.

[0075] Table 1 shows the production conditions for this comparative example, Table 2 shows the properties of the obtained sodium ferrite particles, and Table 3 shows the fixation and recovery performance and dispersibility of carbon dioxide.

[0076] [Table 1]

[0077] [Table 2]

[0078] [Table 3]

[0079] As described above, it is clear that the sodium ferrite particles according to the present invention are a solid carbon dioxide recovery material that is excellent in adsorption and desorption of carbon dioxide. In addition, it is also clear that the particles have excellent dispersibility, and therefore are excellent in moldability and processability. [Industrial Applicability]

[0080] The sodium ferrite particles according to the present invention are a material for fixing and recovering greenhouse gases, particularly carbon dioxide, as part of measures against global warming, and are suitable as a material capable of fixing and recovering carbon dioxide by adsorption and desorption using a non-hazardous inorganic material without using a hazardous material such as an amine aqueous solution.

Claims

1. Na 2 [Zn(OH) 4 ] and Na 2 SnO 2 and a molar ratio of Na / Fe of 1.0 to 1.

5.

2. 2. The sodium ferrite particles according to claim 1, wherein the axial ratio of the average major axis diameter to the average minor axis diameter of the primary particles is 1 to 2.

3. The sodium ferrite particles according to claim 1 or 2, wherein the powder has a pH value of 8 to 14.

4. 4. A method for producing sodium ferrite particles according to claim 1, comprising the step of mixing at least one metal compound particle powder selected from a group consisting of divalent metals consisting of zinc and tin, iron oxide particle powder and sodium raw material particle powder, and subjecting the mixture to a water vapor solid-phase reaction at a temperature of 150° C. to 400° C.

Citation Information

Patent Citations

  • Method for removing carbon dioxide in waste combustion gas

    JP1993301023A

  • Carbon dioxide absorber, method and apparatus for absorbing carbon dioxide, carbon dioxide separator, and process for producing lithium composite oxide

    JP2005270842A

  • Method for separating and recovering carbon dioxide and separating and recovering apparatus of carbon dioxide

    JP2006298707A

  • Active material for sodium secondary battery, and method for producing the same

    JP2008260666A

  • Efficient recovering method of carbon dioxide in exhaust gas

    JP2009006275A